Anxiety Factors of Students’ Emotional Disposition to Professional Communication in Foreign Languages - Buchatska, Svitlana (East European Journal of Psycholinguistics, 2015)
The article deals with the problem of the development of personality’s psychological disposition to professional foreign languages communication. The present research aims to define the concept of personality’s emotional and volitional disposition and reveal its essence and study the formation features of the above mentioned disposition of students of different specialties. The study focuses on the causes and dynamics of the students’ emotional and volitional disposition to professional communication in foreign languages. Emotional disposition is viewed as personality’s ability to adjust his/her behavior and activity in any professional situations by means of foreign language communication. The research results revealed certain difficulties, and therefore the students’ negative experiences in foreign languages communication, which are determined by a high degree of speech fluency, difficulty in understanding spoken language and grasping the meaning of an utterance. The article introduces the reasons for the development of a special program to form students’ emotional and volitional disposition to professional communication in foreign languages. The program is to contain a set of lessons, assignments and trainings aimed at developing the appropriate volitional qualities, psychic self-regulation skills of a personality. References Bondarenko, O. (2004). Psykholohichni osoblyvosti profesijnoho spilkuvannia vijskovosluzhbovtsiv v osoblyvuh umovah diyalnosti [Psychological Features of Professional Communication of Servicemen under Extreme Conditions]. Ph.D. thesis. Khmelnytskyi: DPSU. Bondarenko, O., Volobuyeva, O. (2004).Typova model mizhprofesijnoi komunikatsii [Typical Model of Inter-professional Communication]. Scientific Papers, 28(2), 24-26. Pavlyk, O. (2004). Profesijno-orientovane inshomovne chytannia u riznyh sytuatsiah perekladu yak skladnoho vydu movlennevoi diyalnosti [Professionally oriented foreign reading in different situations of translation as a complex kind of speech activity]. Philolohichni Studii, 106- 111. Prikhozhan, A.M. (1987). Diagnostika lichnostnoi trevozhnosti I nekotorye sposoby eyo preodolenia [Personal Anxiety Diagnostic and Some Methods of Its Overcoming]. Moscow: Moscow State University. Teteruk, S. (2006). Formuvannia mehanizmiv samorehuliatsii studentiv v inshomovnomu prostori [Forming Mechanisms of Self-Regualing in Students in Foreign Environment]. Ph. D. thesis. Kyiv: Drahomanov National Pedagogical University of Kyiv. Gardner, R. C., Tremblay, P.F., & Masgoret, A.M. (1997). Towards a full model of second language learning: An empirical investigation. Modern Language Journal, 81(3), 344-362. MacIntyre, P.D. & Gardner, R.C. (1991) Methods ans results in the study of anxiety and language learning: A review of the literature. Language Learning, 41,1, 85-117. Spielberger, C.D. (1983). Manual for the State-Trait Anxiety Inventory (Form Y). Palo Alto, California: Consulting Psychologists Press.